Hate Speech In Primary Education: Its Implications For Cognitive And Emotional Learning (Journal of Namibian Studies : History Politics Culture, 2023)
The Peruvian education system in general and primary education in particular, in the post-pandemic stage, has been going through one of the most critical moments due to the increase in the social gap and access to technology by students, which is expressed in the heterogeneity in learning reinforced with discriminatory positions that lead to manifestations of hatred.  This study aims to determine the influence of hate speech on cognitive learning and emotional learning of students in the fifth and sixth grades of Primary Education. The methodology used responds to a field study with a sample of 128 students from the two grades of study, a dichotomous questionnaire is administered and another adapted to the Likert scale referring to the dimensions of hate speech, cognitive and emotional learning. Among the results stand out: more than 50% achieved medium or low emotional learning, the average cognitive learning is regular (11,664), there is a negative relationship between hate speech and emotional learning of students. It is concluded that the practice of discourse among students in the fifth and sixth grade of primary education significantly influences their level of cognitive and emotional learning, a fact that has implications for their personal, social and intellectual training.